FORMULATION AND ASSESSMENT OF A PIPER BETLE EMULGEL FOR ANTIMICROBIAL APPLICATION - Prerna Gupta; Alka Maral; Dr. Vishal Dubey; Shailesh Yadav; Shivani Rajbhar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The increasing resistance of microbial strains to existing antimicrobial agents necessitates innovative approaches for effective treatment. This research aims to formulate and evaluate an antimicrobial emulgel using Piper betle leaf extract. The study involved a multi-step methodology comprising leaf collection, extraction, ash value assessment, and phytochemical screening. The emulgels were then formulated using various polymers like Carbopol 934, Carbopol 940, and HPMC. Subsequent physicochemical characterizations were conducted to assess parameters such as pH, viscosity, spreadability, and in vitro drug release. The results revealed a wealth of bioactive compounds in the extract and promising physicochemical properties in the formulated emulgels. The in vitro drug release profiles demonstrated a controlled release mechanism. The findings validate the potential applicability of Piper betle leaf extract-based emulgels in antimicrobial therapy, warranting further research and clinical trials.